The effects of alpha-tocopherol supplementation on fracture healing in a postmenopausal osteoporotic rat model (Clinics, 2012)
OBJECTIVE: Osteoporosis increases the risk of bone fractures and may impair fracture healing. The aim of this study was to investigate whether alpha-tocopherol can improve the late-phase fracture healing of osteoporotic bones in ovariectomized rats. METHOD: In total, 24 female Sprague-Dawley rats were divided into three groups. The first group was sham-operated, and the other two groups were ovariectomized. After two months, the right femora of the rats were fractured under anesthesia and internally repaired with K-wires. The sham-operated and ovariectomized control rat groups were administered olive oil (a vehicle), whereas 60 mg/kg of alpha-tocopherol was administered via oral gavage to the alpha-tocopherol group for six days per week over the course of 8 weeks. The rats were sacrificed, and the femora were dissected out. Computed tomography scans and X-rays were performed to assess fracture healing and callus staging, followed by the assessment of callus strengths through the biomechanical testing of the bones. RESULTS: Significantly higher callus volume and callus staging were observed in the ovariectomized control group compared with the sham-operated and alpha-tocopherol groups. The ovariectomized control group also had significantly lower fracture healing scores than the sham-operated group. There were no differences between the alpha-tocopherol and sham-operated groups with respect to the above parameters. The healed femora of the ovariectomized control group demonstrated significantly lower load and strain parameters than the healed femora of the sham-operated group. Alpha-tocopherol supplementation was not able to restore these biomechanical properties. CONCLUSION: Alpha-tocopherol supplementation appeared to promote bone fracture healing in osteoporotic rats but failed to restore the strength of the fractured bone.